Analisis Pengaruh Kualitas Produk dan Strategi Distribusi Terhadap Penjualan Pada PT Temprina Media Grafika Bekasi - Yohanes Sugiyanta; Muhamad Rohadi (Mulia Pratama, 2023)
This study aims to analyze the Effect of Product Quality (X1), Distribution (X2) of Sales Volume (Y) Study on PT Temprina Media Grafika Bekasi The data used in this study are primary data. In this study, the sampling method using the Non Probability Sample method is Purposive Sampling. The results of this study indicate that Product Quality (X1), Distribution (X2) simultaneously have a positive significant effect on Sales Volume (Y) on PT Temprina Media Grafika Bekasi.